Comparative evaluation of the surface hardness of different esthetic restorative materials: An in vitro study - Anoop Samuel; Rinsa Raju; K B Sreejith; Binitha M Kalathil; Deepthi Nenavath; V S Chaitra (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of this study was to evaluate the surface hardness of a newly developed fiber-reinforced composite and bulkfill composites. Materials and Methods: Fiber-reinforced composite and other commercially available bulkfill composites were used. Fifteen cylindrical specimens (5 mm × 5 mm) were made from each material in metal template. Molds were filled in one increment for both bulkfill composites and fiber-reinforced composite and cured using Ivoclar blue phase light-curing unit at a wavelength of 850 mW/cm2. A dark container was used to store specimens to keep dry at room temperature for 24 h before testing. Vickers hardness number (VHN) on the top and bottom surfaces of each specimen was measured by a microhardness tester. Data for VHN were analyzed by using analysis of variance (ANOVA) and pair-wise Newman-Keuls test. Results: No significant difference was observed in Vickers hardness test. The mean value of VHN on the top and bottom surfaces showed significant difference from each other. Fiber-reinforced composite showed the highest VHN as compared with other materials. Conclusion: Fiber-reinforced composite has the highest Vickers hardness ratio indicating highest degree of conversion and better clinical performance.